LH, Progesterone, and TSH can Stimulate Aldosterone In Vitro: A Study on Normal Adrenal Cortex and Aldosterone Producing Adenoma - Nicolini, G.; Balzan, S.; Morelli, L.; Iacconi, P.; Sabatino, L.; Ripoli, A.; Fommei, E. (Hormone and Metabolic Research, 2014)
Endocrine factors different from ACTH or angiotensin II can stimulate aldosterone secretion and have a role in the pathophysiology of hyperaldosteronism. Aldosterone may increase in luteotropic/progestogenic and in hypothyroid states; LH and, occasionally, TSH receptors have been detected in normal adrenal cortex and aldosterone-producing adenoma. The aim of the study was to compare adrenal contents of LH and TSH receptors between normal cortex and aldosterone-producing adenoma and to evaluate the ability of LH, its product progesterone, and TSH to stimulate aldosterone secretion in vitro from primary adrenocortical cells. Surgical aldosterone-producing adenoma fragments from 19 patients and adrenal cortex fragments from 10 kidney donors were used for Western blotting and cell cultures. LH (n=26), TSH (n=19) and progesterone (n=8) receptor proteins were investigated; LH receptor-mRNA was also tested in 8 samples. Aldosterone responses in vitro to LH, progesterone, and TSH stimulation were assayed. LH and TSH receptors were more expressed in adenoma than normal cortex (p<0.01, p<0.05, respectively); progesterone receptor was observed in 6/8 samples. Aldosterone increased after in vitro stimulation with LH (5/12 adenoma, 1/7 normal cells), progesterone (4/5 adenoma, 5/6 normal cells), and TSH (3/5 adenoma and 3/5 normal cells). LH and TSH receptors were more expressed in aldosterone producing adenoma than normal adrenal cortex. LH, progesterone, and TSH can stimulate aldosterone in vitro. Similar mechanisms could participate in vivo in the aldosterone increase in lutheotropic, progestogenic, or hypothyroid states and may exist in both normal adrenal cortex and adenoma in responsive individuals.
Keywords: LH receptor; TSH receptor; progesterone; aldosterone